Thyroid Surgery in a Resource‐Limited Setting: Feasibility and Analysis of Short‐ and Long‐term Outcomes. (27th December 2016) - Jafari, Aria; Campbell, David; Campbell, Bruce H.; Ngoitsi, Henry Nono; Sisenda, Titus M.; Denge, Makaya; James, Benjamin C.; Cordes, Susan R.
Abstract : Objective: The present study reviews a series of patients who underwent thyroid surgery in Eldoret, Kenya, to demonstrate the feasibility of conducting long‐term (>1 year) outcomes research in a resource‐limited setting, impact on the quality of life of the recipient population, and inform future humanitarian collaborations. Study Design: Case series with chart review. Setting: Tertiary public referral hospital in Eldoret, Kenya. Subjects and Methods: Twenty‐one patients were enrolled during the study period. A retrospective chart review was performed for all adult patients who underwent thyroid surgery during humanitarian trips (2010‐2015). Patients were contacted by mobile telephone. Medical history and physical examination, including laryngoscopy, were performed, and the SF‐36 was administered (a quality‐of‐life questionnaire). Laboratory measurements of thyroid function and neck ultrasound were obtained. Results: The mean follow‐up was 33.6 ± 20.2 months after surgery: 37.5% of subtotal thyroidectomy patients and 15.4% of lobectomy patients were hypothyroid postoperatively according to serologic studies. There were no cases of goiter recurrence or malignancy. All patients reported postoperative symptomatic improvement and collectively showed positive pre‐ and postoperative score differences on the SF‐36. Conclusion: Although limited by a small sample size and the retrospective nature, our study demonstrates the feasibility of long‐term surgical and quality‐of‐life outcomes research in a resource‐limited setting. The low complication rates suggest minimal adverse effects of performing surgery in this context. Despite a considerable rate of postoperative hypothyroidism, it is in accordance with prior studies and emphasizes the need for individualized, longitudinal, and multidisciplinary care. Quality‐of‐life score improvements suggest benefit to the recipient population.